PENINGKATAN KUALITAS KARYAWAN GUNA MENINGKATKAN KEPUASAN PELANGGAN BINATU SEMARANG LAUNDRY & DRY CLEANER - Handhini, Lutfika Nur; Niati, Asih; Amalia, Naini Rizka (Solusi, 2022)
The problem in this study is motivated by the decline in customer satisfaction and loyalty which is marked by the decline in sales turnover and from some of the results of the research gap that results in different research results. The purpose of this study is to find out how to improve employee quality to increase customer satisfaction. This study uses qualitative methods, using triangulation of sources with interviews and triangulation of methods namely interviews, observation and documents as evidence. The object of research is Binatu Semarang Laundry. There are 6 informants in this study consisting of owners, employees and customers. From the results of this study indicate that there are still some problems in the quality of Human Resources (HR) such as not obeying procedures. workloads are too heavy, work stress, old or damaged machines and tools that hinder work causing quality problems. This ultimately affects customer satisfaction so there needs to be improvements